Chimeric spider silk proteins mediated by intein result in artificial hybrid silks. Issue 7 (July 2016) - Lin, Senzhu; Chen, Gefei; Liu, Xiangqin; Meng, Qing
ABSTRACT: Hybrid silks hold a great potential as specific biomaterials due to its controlled mechanical properties. To produce fibers with tunable properties, here we firstly made chimeric proteins in vitro, called W2C4CT and W2C8CT, with ligation of MaSp repetitive modules (C) with AcSp modules (W) by intein trans splicing technology from smaller precursors without final yield reduction. Intein mediated chimeric proteins form fibers at a low concentration of 0.4 mg/mL in 50 mM K3 PO4 pH 7.5 just drawn by hand. Hybrid fibers show smoother surface, and also have stronger chemical resistance as compared with fibers from W2CT (W fibers) and mixture of W2CT/C8CT (MHF8 fibers). Fibers from chimeric protein W2C4CT (HFH4) have improved mechanical properties than W fibers; however, with more C modules W2C8CT fibers (HFH8) properties decreased, indicates the length proportion of various modules is very important and should be optimized for fibers with specific properties. Generally, hybrid silks generated via chimeric proteins, which can be simplified by intein trans splicing, has greater potential to produce fibers with tunable properties. Our research shows that intein mediated directional protein ligation is a novel way to make large chimeric spider silk proteins and hybrid silks. © 2016 Wiley Periodicals, Inc. Biopolymers 105: 385–392, 2016.